Factors Affecting the Implementation of Canal Blocking Development as A Fire Prevention Solution In River Village Tohor Regency - Febri Yuliani; Nova Erlina (Policy & Governance Review, 2018)
The area of forest and burning land in Riau Province until 2016 has reached 3,218 hectares with the highest number of fires in Rokan Hilir Regency with 32 points. Other fire spots are also spread in Pelalawan, Meranti, Rokan Hulu, Bengkalis, Inhil, and Inhu districts. Meanwhile, forest fires and peat lands in the eastern coastal region also continue. Up to now, there have been 310.25 hectares of peat land already burned in Meranti Regency. To know and analyze the factors that influence the development of canal blocking as a peat land fire prevention solution in Sungai Tohor village, Kepulauan Meranti regency. The type of this research is qualitative with explorative method. In the construction of canal blocking as a peat land fire prevention solution in Sungai Tohor Village is influenced by several factors. The first is the government regulation factor, community participation in the form of participation and public awareness in the construction of canal blocking. As well as public awareness as a subject who felt the benefits of the existence of this blocking canal. Next is the local wisdom of peat communities. Which communities should maintain the sustainability of peat lands that are the source of their lives that have traditionally used them to cultivate sago.